Accumulation of lead in lampam jawa (Puntius gonionotus, Blk) - Rohani Ibrahim (Fakulti Pengajian Maritim dan Sains Marin, 2011)
The accumulation of lead in various organs of Lampam Jawa(Puntius gonionotus) was studied as a function of different lead concentrations. Aquarium tanks of 70 liters capacity were used in holding the fishes with 20 fishes in each tank.